Redescription of Excirolana armata (Dana, 1853) and synonymy of Cirolana argentina Giambiagi, 1930 (Crustacea: Isopoda: Cirolanidae) - Ribetti, Virginia L. (2006)
Excirolana armata (Dana, 1853) is redescribed on the basis of material collected from Puerto Quequén, Argentina, the type locality of Cirolana argentina Giambiagi, 1930. Based on this material, it is concluded that C. argentina is a junior synonym of E. armata. The distribution of E. armata is extended from Rio de Janeiro to Golfo San José (northern Patagonia). Excirolana armata is most similar to the Chilean species Excirolana hirsuticauda Menzies, 1962 and Excirolana monodi Carvacho, 1977; a table comparing these three species is provided. The male second pleopod and pleotelson of E. hirsuticauda are illustrated.